IMPACT OF THE BARIATRIC SURGERY ON THE MORFOLOGIC VARIABLES OF MORBID OBESE (Fiep Bulletin - online, 2014)
The progress of the scientific knowledge on the increase of the morbimortality originating from the morbid obesity emphasizes the need of medical intervention in the treatment of this disease. In this aspect, the surgeries for control of the morbid obesity are justified as a current method that controls in effective way, in the medium and long term, the weight excess. Objective: To verify the impact of the bariatric surgery in the corporal composition of obese morbid in different moments after the surgical intervention. Methods: 30 patients submitted to the bariatric surgery were analyzed. The patients were appraised in the preoperative (T0) and 30 (T30), 90 (T90)  and 180 (T180) days after the surgery. With the anthropometric method, the following parameters were obtained: total corporal mass, relative corporal fat (%), lean corporal mass (LCM), fat corporal mass (FCM) and basal metabolic rate (BMR). Results: there was significant difference (p=0,05) for all the variables analyzed in all of the considered times. Conclusions: the bariatric surgery has been efficient in relation to the loss of absolute weight and reduction of the corporal fat mass in all of the moments. However, it is important to note that the significant reduction in the lean corporal mass and basal metabolic rate can represent a problem in the maintenance of the patients weight during the post-surgery period. The regular practice of physical activity together with a set of dietary measures are recommended to help reducing the impact of the surgery in the corporal composition.
Keywords: obesity; corporal composition; bariatric surgery